2021
DOI: 10.3390/cancers13122889
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-Mesenchymal Transition Enhances Cancer Cell Sensitivity to Cytotoxic Effects of Cold Atmospheric Plasmas in Breast and Bladder Cancer Systems

Abstract: Cold atmospheric plasma (CAP) has emerged as a highly selective anticancer agent, most recently in the form of plasma-activated medium (PAM). Since epithelial–mesenchymal transition (EMT) has been implicated in resistance to various cancer therapies, we assessed whether EMT status is associated with PAM response. Mesenchymal breast cancer cell lines, as well as the mesenchymal variant in an isogenic EMT/MET human breast cancer cell system (PMC42-ET/LA), were more sensitive to PAM treatment than their epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 68 publications
2
43
0
Order By: Relevance
“…These metrics have been helpful in investigating the association of EMT/MET with other axes of cellular plasticity such as stemness (Bocci et al, 2018), immune evasion (Li et al, 2019) and sensitivity to anti-cancer agents (Wang et al, 2021). Intriguingly, EMT status of primary tumors was not found to be universally correlated with worse patient survival, but instead showed a context-dependent trend, consistent with previous reports (Tan et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…These metrics have been helpful in investigating the association of EMT/MET with other axes of cellular plasticity such as stemness (Bocci et al, 2018), immune evasion (Li et al, 2019) and sensitivity to anti-cancer agents (Wang et al, 2021). Intriguingly, EMT status of primary tumors was not found to be universally correlated with worse patient survival, but instead showed a context-dependent trend, consistent with previous reports (Tan et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Future efforts should also consider how these metrics can be adapted to investigate different cell-state transition trajectories, for instance, by defining a two-dimensional (2D) EMT score that can deconvolute gains in the mesenchymal program vs. losses in the epithelial one [ 97 ]. The three EMT scoring metrics have been helpful in investigating the association of EMT/MET with other aspects of cellular plasticity such as stemness [ 98 ], immune evasion [ 99 ], and sensitivity to anti-cancer agents [ 100 ]. However, future work remains to be conducted on how to connect these data-based metrics with insights from mechanism-based dynamical models of EMT [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous report demonstrated that CAP did not induce changes in the expression of vimentin in the pancreatic cancer cell lines PaTuS and PaTuT in vitro, whereas in three-dimensional spheroids of Mia PaCa-2 and RLT-PSC co-cultures, CAP did not enhance the migration of either cell population outside the spheroids [27]. Previous studies on breast cancer cell lines have suggested that direct and indirect application of CAP could inhibit EMT, being more effective against those with a mesenchymal phenotype [56,57]. In addition, the combination of CAP with silymarin nano emulsion on melanoma cells decreased the expression of EMT markers while reducing the tumour weight and size [58].…”
Section: Discussionmentioning
confidence: 94%